Lactic acid fermentation of pasteurized and powdered milk and optimizing the factors affecting the fermentation process - Sharar, Nowshin Shyara (BRAC University, 2014)
A Thesis submitted to BRAC University in partial fulfillment of the requirements for the Bachelors degree in Microbiology